perbandingan kurikulum merdeka dan kurikulum 2013 terhadap peningkatan kreativitas peserta didik di SMPN 21 Mataram - Saputri, Tri; Rispawati; Basariah; Mustari, Mohammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the comparison between the Merdeka Curriculum and the 2013 Curriculum on enhancing students' creativity. The research employed a quantitative approach with an ex-post facto design. The sample consisted of two classes selected through purposive sampling technique, namely class VIII A with 25 students and class IX A with 27 students. The research instrument was a validated and reliable creativity enhancement questionnaire. Data were analyzed through prerequisite tests (Kolmogorov-Smirnov normality test and homogeneity significance test), followed by hypothesis testing using One-Way ANOVA. The analysis results showed a significance value of 0.017 < 0.05, with a mean score of students' creativity enhancement of 44.120. These findings indicate that there is a significant difference between the Merdeka Curriculum and the 2013 Curriculum in terms of enhancing students' creativity.